Laporan Pendidikan Kesehatan Kebutuhan Nutrisi Untuk Proses Penyembuhan Luka Post OP di Bangsal Mawar RSUD Dr Soehadi Prijonegoro Sragen - Nadia Selli Putri Utami; Devita Mayaningrum; Ika Widya Ning Tias; Irma Mustika Sari; Supanti Supanti (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
: Background: Nutrients are obtained from food and fluids which are then assimilated by the body. Nutrition itself is one of the factors that can support the wound healing process, there are things that are no less important that must be considered as well, namely the nutrients from the food we eat during the wound healing process. Objective: The purpose of postoperative diet is to strive for the patient's nutritional status to return to normal immediately to accelerate the healing process and increase the patient's immune system, by providing basic needs (fluids, energy, protein), replacing the loss of protein, glycogen, iron, and other nutrients, correcting electrolyte and fluid imbalances, preventing and stopping bleeding. Methods: The media used in health education activities is leaflets. Through leaflets we hope that the delivery of material can be understood by participants and can be delivered well.Results: The results of observations from this health education activity, that the majority of participants are active in asking questions and answering questions given by the health education team and can explain the essence of the material that has been delivered by the speaker Conclusion: Of the 20 patient families who attended 15 people had understood the fulfillment of nutritional needs for the correct post op wound healing process.